Vacuum arc deposition of TIN and TIOx films on large metallic and dielectric surfaces; Proceedings of the 17th International Symposium on Discharges and Electrical Insulation in Vacuum, ISDEIV, Berkeley, CA, july 21-26, 1996; Vol. 2 - Borisov D. P.; Koval N. N. Nikolay Nikolaevich; Kovsharov N. F.; Tolkachev V. S.; Schanin P. M. (1996, 1996)
Plasma-assisted vacuum deposition of TiN and TiOx films is performed using four vacuum arc evaporators and four hot-cathode-arc plasma generators. Film deposition on substrates of total area 6 m2 , with the workpiece having dimensions of 1?1.6 m, is completed in one cycle. The arc parameters in the process of film deposition are typically as follows: the vacuum arc current and voltage are 100 A and 30 V, respectively, and the hot-cathode arc current and voltage are 20 A and 50 V, respectively. The deposition of a TiN film on a metal takes 50 min, while the TiN or TiOx film deposition on a dielectric occurs within 20 min.